Generating autologous hematopoietic cells from human-induced pluripotent stem cells through ectopic expression of transcription factors. Issue 4 (July 2017) - Hwang, Yongsung; Broxmeyer, Hal E.; Lee, Man Ryul
Abstract : Purpose of review: Hematopoietic cell transplantation (HCT) is a successful treatment modality for patients with malignant and nonmalignant disorders, usually when no other treatment option is available. The cells supporting long-term reconstitution after HCT are the hematopoietic stem cells (HSCs), which can be limited in numbers. Moreover, finding an appropriate human leukocyte antigen-matched donor can be problematic. If HSCs can be stably produced in large numbers from autologous or allogeneic cell sources, it would benefit HCT. Induced pluripotent stem cells (iPSCs) established from patients' own somatic cells can be differentiated into hematopoietic cells in vitro . This review will highlight recent methods for regulating human (h) iPSC production of HSCs and more mature blood cells. Recent findings: Advancements in transcription factor-mediated regulation of the developmental stages of in-vivo hematopoietic lineage commitment have begun to provide an understanding of the molecular mechanism of hematopoiesis. Such studies involve not only directed differentiation in which transcription factors, specifically expressed in hematopoietic lineage-specific cells, are overexpressed in iPSCs, but also direct conversion in which transcription factors are introduced into patient-derived somatic cells which are dedifferentiated to hematopoietic cells. As iPSCs derived from patients suffering from genetically mutated diseases would express the same mutated genetic information, CRISPR-Cas9 gene editing has been utilized to differentiate genetically corrected iPSCs into normal hematopoietic cells. Summary: IPSCs provide a model for molecular understanding of disease, and also may function as a cell population for therapy. Efficient differentiation of patient-specific iPSCs into HSCs and progenitor cells is a potential means to overcome limitations of such cells for HCT, as well as for providing in-vitro drug screening templates as tissue-on-a-chip models.